The role of superior capsular approach (SuperPATH) in the treatment of femoral neck fractures with hemiarthroplasty implantation: our experience and review of literature - Scaglione, Michelangelo; Casella, Francesco; Giuntoli, Michele; Celli, Fabio; Fabbri, Luca; Marchetti, Stefano (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: since 2003, a series of so called ‘micro-posterior’ approaches have been developed in the orthopaedic surgery to perform total hip replacement. These techniques present several theoretical advantages compared to the classic postero-lateral approach: reduction in blood loss, post-operative pain, and length of stay but also improving functional outcomes. In our hypothesis these goals could also be obtained in patients with femoral neck fractures, especially in the elderly with several comorbidities.Methods: In our series we performed 50 consecutive cemented hemiarthroplasties through SuperPATH approach. At the latest follow-up (FU) 41 patients were included in the study. Clinical and radiological evaluation was performed before the surgery and at the latest FU using VAS score, Harris Hip Score (HHS) and conventional AP and LL X-rays.Results: We didn’t report any intra-operative complication (i.e. periprosthetic fractures, vasculo-nervous injuries or dislocations) or any case with a dysmetria greater than 1 cm. Mean blood transfusion units were 0.8 during surgery (0 – 4) and 1,6 after surgery (0-4). We reported a mean length of stay of 9.7 days (range 7-15) mainly due to our patients’ high comorbidity rate. At the last one-year FU no cases of dislocation, infection and clinical or radiographical signs of prosthetic loosening were recorded. All our patients returned to the same activity level before femoral fracture occurred, according to HHS.Conclusion: The SuperPATH is a real minimally invasive approach with a low rate of intra- and post-operative complications. It is related to a reduced dislocation rate and potentially to a reduced infection rate compared to the conventional surgical approaches, allowing, furthermore, a faster functional recovery. According to our experience the advantages of this type of approach can be obtained in the trauma field too.